Relationship Between Pregnant Women's Knowledge of Danger Signs and Compliance with Antenatal Care at Ternate City Health Center - Djalinalbun Kalunalr; Sulistiyah Sulistiyah; Tut Rayani Aksohini (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
Pregnancy is a critical period that begins with conception and lasts until the birth of the fetus, typically lasting about 280 days. Adequate antenatal care (ANC) is essential to ensure the healthy development of the fetus and to identify potential complications early. One of the most important factors contributing to maternal and fetal health is the level of knowledge pregnant women have regarding pregnancy-related danger signs. This study aims to analyze the relationship between pregnant women’s knowledge of pregnancy danger signs and their compliance with attending ANC visits at the Ternate City Health Center. This research employed a qualitative design with a cross-sectional approach to examine the knowledge and compliance of pregnant women within the area. A total sampling technique was used, where the sample size was equivalent to the population size. Data were analyzed using the Chi-square test to determine any significant relationships between the variables. The results of the analysis showed a significant relationship between the pregnant women’s knowledge of pregnancy danger signs and their adherence to ANC visits. The statistical analysis indicated a p-value of 0.003 (p < 0.05), demonstrating a strong correlation between the two factors. This finding highlights the importance of educating pregnant women about the danger signs of pregnancy, as better awareness may lead to higher rates of ANC attendance. Furthermore, the study emphasizes the role of healthcare providers in disseminating critical information to expectant mothers, ensuring they recognize the importance of timely ANC visits. In conclusion, increasing knowledge about pregnancy-related danger signs among pregnant women is crucial for improving maternal health outcomes and promoting better compliance with ANC visits, ultimately leading to healthier pregnancies.